The Association between Depression Severity, Prosody, and Voice Acoustic Features in Women with Depression - Mohammad-Sadegh Seifpanahi; Tina Ghaemi; Ali Ghaleiha; Davood Sobhani-Rad; Mohammad-Kazem Zarabian (The Scientific World Journal)
The aim was to define the association between the severity of depression, prosody, and voice acoustic features in women suffering from depression and its comparisons with nondepressed people. Prosody and acoustic features in 30 women with major depression hospitalized in a psychiatric ward and 30 healthy women were investigated in a cross-sectional study. To define the severity of depression, the Hamilton Rating Scale for Depression (HRS-D) was applied. Acoustic parameters such as jitter, shimmer, cepstral peak prominence (CPP), standard deviation of fundamental frequency (SD F0), harmonic-to-noise ratio, and F0 and also some speech prosodic features including the speed of speech, switching pause duration means, and durations of produced sentences with different modals were measured quantitatively. Also, six raters judged the patient’s prosody qualitatively. SPSS V.28 was used for all statistical analyses (p<0.05). There was a significant correlation between HRS-D with jitter, SD F0, speed of speech, and switching pause means (p≤0.05). The means of CPP and duration of producing emotional sentences differed between the depression and control groups. The HRS-D scores were significantly correlated with switching pauses in patients (Pearson coefficient = 0.47, p=0.05). The results of the perceptual evaluation of prosody judged by six raters showed an 85% correlation between them (p≤0.001). Some acoustic and prosodic parameters are different between healthy women and those with depression disorder (e.g., CPP and duration of emotional sentences) and may also have an association with the severity of depression (e.g., jitter, SD F0, speed of speech, and switching pause means) in women with depression disorder. It was indicated that the best sentence modal to assess prosody in patients with depression would be exclamatory ones compared to declarative and interrogative sentences.